Impact of biopsy perineural invasion on younger prostate cancer patients after radical prostatectomy. (1st November 2020) - Lin, Sharron X.; Zheng, Yu; Wu, Shulin; Blute, Michael L.; Dahl, Douglas M.; Wu, Chin-Lee
Abstract: Objectives: To identify the potential indicators for higher-risk disease and poor outcome in younger prostate cancer (PCa) patients (age ≤ 50) who had undergone radical prostatectomy (RP) in the prostate-specific antigen (PSA) era. Materials and Methods: A total of 186 PCa cases of age ≤ 50 who underwent RP between 2003 and 2010 at our center were included for study. High-risk disease after RP was defined as cases with pre-PSA ≥ 20 ng/ml and/or Gleason score (GS) ≥ 4 + 3 and/or pT stage ≥ 3. The poor outcome group was defined as cases with biochemical recurrence (BCR) and/or metastasis (Mets) and/or all-cause death. Multivariate logistic regression models were performed to identify independent risk factors for both high-risk disease and poor outcome. Results: Among 186 younger PCa patients aged ≤ 50, 36 cases (19.5%) had high-risk disease and 24 cases (12.9%) had poor outcome. The presence of biopsy perineural invasion (BxPNI) was significantly associated with high-risk disease and showed a trend to correlate with worse outcome in univariate analysis. On multivariate logistic regression analysis, BxPNI was shown to be a significant independent risk factor with covariate of D'Amico for poor outcome ( p = 0.047) and an independent risk factor with covariate of BxGPC for high-risk PCa excepting the variables to define high-risk disease ( p = 0.013). Prognostically, cases with BxPNI showed a poor BCR-free survival in univariate analysis but did not reach significance ( p = 0.063). Conclusion: Our results show that BxPNI could be considered as a risk classification factor to identify the best candidates among younger PCa patients for further treatment and may also be used for developing active surveillance (AS) selection criteria for younger PCa patients.